Protocol for a parallel-group, superiority randomized controlled trial of the PulsePoint mobile application to increase bystander resuscitation in out-of-hospital cardiac arrest - Steven C. Brooks; John M. Tallon; Sandra Jenneson; Ashish R. Panchal; Robert Grierson; Laurie J. Morrison; Damon C. Scales; Andrew Day; Lindsay O’Donnell; Randy S. Wax; Helen Connolly; Jennie Helmer; et al. (Resuscitation Plus)
Out-of-hospital cardiac arrest (OHCA) is a leading cause of mortality. Despite public awareness campaigns, widespread cardiopulmonary resuscitation (CPR) training initiatives, and deployment of public access defibrillators, potentially life-saving bystander intervention occurs inconsistently. Mobile technologies that alert nearby lay responders or off-duty professionals to OHCA events have emerged as a strategy to increase bystander CPR and AED use. The PulsePoint Randomized Controlled Trial (RCT) is a multi-centre pragmatic RCT designed to evaluate whether alerts sent via the PulsePoint Respond mobile application increase the likelihood of bystander resuscitation attempts before paramedic arrival.The trial is being conducted within a province-wide Canadian paramedic service and a municipal fire rescue service in the USA. Eligible 9-1-1 calls for suspected non-traumatic OHCA occurring in a public (non-residential) location are randomized in real time to activation or suppression of the PulsePoint system. The primary outcome is bystander CPR or AED use prior to paramedic or firefighter arrival. Patients are included in the primary analysis if they are determined to have paramedic-treated OHCA in a public location with at least one PulsePoint user within 400 m. The target sample size is 340 patients powered at 80 % to detect a 15 % absolute increase in the primary outcome.This pragmatic trial addresses a critical evidence gap in resuscitation science. We anticipate findings will inform refinement of technology implementation, policy, guideline development, and system-level decisions regarding the implementation of mobile alert systems to improve early intervention and survival from OHCA.